The implementation of indoor child monitoring system using trilateration approach - Normazatul Shakira, Darmawati; Nurul Hazlina, Noordin (Asian Research Publishing Network (ARPN), 2015)
This paper presents the child monitoring system by implementing one of the indoor positioning techniques. Over the years, there have been numerous reports on missing children in crowded areas such as in shopping complexes. One of the reasons is the difficulty to monitor these children and this demands a system that could enable parents to track their children’s whereabouts. Unlike outdoor monitoring system which makes use of the GPS signals, indoor positioning system makes use of the Wi-Fi signals. The aim of this project is to implement an Indoor Positioning System that is able locate their child in a confined space as Global Positioning System are limited to outdoor tracking. The proposed system will be based on Wi-Fi signal strength that uses trilateration technique to calculate the exact location of the child. . The proposed system uses three access points and the strength of the WI-FI signals at each access points is used in order to calculate the position of the children. The system is implemented using Intel Galileo Development board. The measured results of the proposed system achieved 90% accuracy.